Developing Scramble Words Game to Teach Writing Skill of Seventh Grade in Junior High Shool - Putri Arnetta Priscilla; Makrifah Istina Atul; Saifudin Ahmad; Widiarini (JOSAR (Journal of Students Academic Research), 2026)
The goal of this project is to create a Scramble Words game as a teaching tool to help seventh-grade students become better writers. It was inspired by pupils' poor sentence structure, poor use of proper language, and lack of enthusiasm for writing assignments. The research and development (R&D) design used in this study was modified from Borg and Gall and included needs analysis, design, development, implementation, and assessment. Fourteen seventh-grade students from SMP Islam Baabussalaam served as the subjects, and information was gathered via questionnaires, documentation, and observation. Word cards, worksheets, and teacher recommendations are included in the product, which is offered in both printed and digital formats and is intended to assist students in creating coherent sentences and paragraphs. The findings demonstrate how well the Scramble Words Game enhances pupils' writing. The results show that the Scramble Words Game effectively improves students’ writing skills, including sentence construction, vocabulary use, and idea organization, while also increasing motivation and participation. In conclusion, the Scramble Words Game is a valid, practical, and effective medium for teaching writing and can be used as an alternative strategy to create a more interactive and enjoyable learning environment.